Determinants of Student Self-Confidence: Student Facilitator and Explaining (SFE) Learning Model Approach Based on Mind Mapping - Rini Siti Masitoh; Huliman Abdul Gofur; Mutia Fitri Hanum (Amandemen: Journal of Learning, Teaching and Educational Studies, 2025)
This research was motivated when the learning process took place, it was often found that there was a tendency for students not to ask the teacher even though they did not understand the material presented by the teacher, students lacked confidence to express opinions or ideas in front of the class. This may be due to the strategies used by teachers in teaching, sometimes these students feel bored with the same way of learning, they want a new way of learning with additional models, methods or media that are fun, but the learning process continues to be conducive, effective. and efficient. Based on this background, this study aims to determine the effect of the application of the Mind Mapping-Based Student Facilitator And Explaining (SFE) Learning Model on the Confidence of MAN 1 Bandung Students in Akidah Akhlak Subjects. The research method uses a quantitative approach. The population in this study were all students of MAN 1 Bandung, totaling 262 students, while the sample in this study was 74 students. Techniques Data collection is done by means of a questionnaire. The data analysis technique uses Regression Analysis with processing using the IBM Statistical Package for Social Sciences (SPSS) Version 25.0 software for Windows. The results showed that 9.8% of students' self-confidence was influenced by the use of the Student Facilitator And Explaining (SFE) Learning Model Based on Mind Mapping (X).